BRICS' enlargement: Power expansion or contraction in a changing world order? - Pádraig Carmody (EconPol Forum, 2024)
The BRICS' expansion should be seen in the context of an ongoing challenge to the international order in general, and the West's competition with China and Russia in particular. China views the current difficulties of the liberal international order as a moment of "strategic opportunity," prompting it to try to create new alliances to garner support as its economy stumbles and it experiences geopolitical pushback. Given that oil remains central to the functioning of the world economy, the admission of new major producers into the bloc will potentially advance the members' energy security and de-dollarization agendas. Whatever coherence the group had will now be further diluted, making the achievement of consensus more difficult. This may be the first of further rounds of enlargement, depending on how this one plays out.
Keywords: 330